Proses Pengelolaan Data Menggunakan Cobit terhadap Peran Audit Internal di BPK Kantor Wilayah Daerah Istimewa Yogyakarta - Chaidir Iswanaji (Universitas Muhammadiyah Malang, 2017)
The audit process is essential to ensure the accountability of local government financial reports.The phenomenon in Indonesia, especially in the financial statements of local government arevery few local governments that receive unqualified notes of CPC. The role of internal audit intospacious with new concepts and rules that developed among other things, software COBIT. Thepurpose of this study was to determine the role of internal audit and the impact of InformationTechnology on data management processes using COBIT to the role of internal audit in BPK. Themethod used is descriptive qualitative. Data were collected by interview, documentation andobservation. The interviews were conducted by two members of the internal audit in BPK. Mechanical analysis of data using the Interactive model analysis. The results of this study are;First, the role of internal audit is not only limited to the examination, but also performs manyfunctions and consulting services in order to improve the performance of CPC. Second, the auditor can use Audit Guidelines as an additional material to design audit procedures. In short, inparticular COBIT guidelines can be modified easily, according to the industry. In conclusion IT asa bridge between the risks of IT with the control needed ( IT risk management) and also the mainreferences were very helpful in the application of IT Governance in the CPC.Keyword: Internal Audit, COBIT and CPC.